Dye promoted electron transfer in DUT-5/BiVO4 heterojunction for organic pollutants degradation. (June 2022) - Zhou, Yi; Li, Jiaxin; Zhang, Jin; Chen, Yongbo; Yao, Tiantian; Chen, Anna; Xiang, Minghui; Chen, Zhiyue; Wu, Zhibin
Highlights: A type 2 heterojunction DUT-5/BiVO4 is fabricated successfully. DUT-5/BiVO4 heterojunction with RhB-sensitized effect. the RhB sensitization process of DUT-5/BiVO4 heterojunction merely affected the DUT-5 instead of BiVO4. RhB act as photosensitizer to enhance visible light absorption and promote electron transfer. RhB/DUT-5/BiVO4 photocatalytic material exhibits enhanced visible light photodegradation activity compare to DUT-5, BiVO4 and DUT-5/BiVO4 . Dye promoted electron transfer in DUT-5/BiVO4 heterojunction for organic pollutants degradation. Abstract: Dye sensitization is a pivotal method for the improvement of light utilization and electron transfer. Herein, a rhodamine B (RhB)-sensitized type Ⅱ DUT-5/BiVO4 heterojunction was successfully synthesized. The results showed that the RhB sensitization process of DUT-5/BiVO4 heterojunction merely affected the DUT-5 instead of BiVO4 . SEM results showed that the regular DUT-5 nanoparticles were homogeneously dispersed on the surface of leaf-shaped BiVO4 nanosheets. The as-fabricated samples were employed to degrade RhB and tetracycline (TC) under 300 W Xe lamp (λ ≧ 420 nm) irradiation. The RhB sensitized heterojunction showed considerably strengthened photocatalytic performance. The photodegradation efficiency of RhB sensitized BD-15% can achieve 82% for RhB after 60 min visible-light irradiation, and 71% for TC after 30 min visible-light irradiation. The dye-sensitized composites exhibit excellent photocatalytic activity ascribed to its boosted photoinduced electron transport, broadened visible-light response range and larger specific surface area. Moreover, a possible mechanism for pollutants photodegradation over RhB sensitized DUT-5/BiVO4 was proposed. Graphical abstract: Image, graphical abstract .